The Role of Psychology in Special Needs Education - fattah hanurawan (Department of Special Education, 2017)
Special needs children are children who have disability, health or mental health or mental health conditions requiring early intervention requiring early intervention and supports. Psychology has important contributions to understanding, explanation, prediction, control, and solves problems of special needs children. The real contributions of the psychology are in a collaborative process with other stakeholders in a children’s bio-psycho-social system. The system involves the children, family, community, educators and educational systems, and other professional. In this context, the contributions of psychologist are best given within a multi-disciplinary group. Psychologists apply psychology theories in understanding, explanation, prediction, control, and solve problems of special needs children. For applied psychologists, theories are the important tool for understanding, explaining, predicting, controlling, and solving problems of special needs children.